Mirrors and Mazes by Howard Thomas Brady - Bauer, Henry (Journal of Scientific Exploration, 2017)
This book raises a number of the points that demonstrate flaws and downright errors in the theory that human-generated carbon dioxide is the chief driver of global warming and climate change. The author has a respectable academic record; he worked and published on the geological and climatic history of the Ross Sea and McMurdo Sound regions of Antarctica, using microscopic fossils as clues. For most of Earth’s history, global temperatures were higher than now by several degrees Centigrade while animal as well as plant life flourished. There has been much more carbon dioxide in the atmosphere than now during lengthy periods when global temperatures were much lower, including in some Ice Ages. Moreover, during roughly half of the last 150 years, temperatures were not rising while carbon dioxide levels were increasing. A common assertion in the mass media and by climate catastrophists is that global warming has already resulted in more frequent and more extreme storms and the like. But the actual data show that extreme weather events have not increased in recent decades; not Atlantic storms, nor Australian cyclones, nor US tornadoes, nor “global tropical cyclone accumulated energy,” nor extremely dry periods in the USA, in the last 150 years during which atmospheric carbon dioxide increased by 40% (pp. 46–51). Nor have sea levels been rising in any unusual manner (Chapter 6). An important point here is that the best data come from local gauges, not from measurements made from satellites, which incorporate several assumptions and inevitable uncertainties.